2009
DOI: 10.1111/j.1475-1313.2009.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of ocular aberrations with gaze

Abstract: The dependence of the ocular aberrations on gaze has been studied in three eyes using a fastacquisition, Hartmann-Shack wavefront sensor. Although there were some trends in the change of some aberration terms with gaze, the changes of most Zernike coefficients were smaller than their variability at each individual gaze position, due to the combined effects of microfluctuations of accommodation, eye movements, tear film dynamics, and measurement noise. For our particular experimental dataset, the confidence lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Several studies have shown that unstable tear films will increase irregular astigmatism and bad optical quality. [35][38] Moreover, HOA changed dynamically with blinking, even in normal subjects. [39] …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that unstable tear films will increase irregular astigmatism and bad optical quality. [35][38] Moreover, HOA changed dynamically with blinking, even in normal subjects. [39] …”
Section: Discussionmentioning
confidence: 99%
“…While studies have shown no significant variation in ocular aberrations with horizontal gaze [6], we hypothesize that downward gaze might be different due to lid pressure [9,1416], gravitational effects [12,13], or perhaps some differences in the biomechanical force from the extraocular muscles. So along with the human eyes, we also measured aberrations from a model eye in primary gaze and downward gaze using the relay lens system to verify that the changes in aberrations found in human eyes in downward gaze were real effects (i.e., optical and physiological changes) rather than representing artefacts induced from the measurement technique.…”
Section: Methodsmentioning
confidence: 94%
“…However, this does not replicate the natural viewing conditions of human eyes for many tasks such as near work or reading that typically involve binocular viewing and near focus (accommodation) in downward gaze. A number of studies [68] have shown that changes in horizontal gaze have no significant influence on the optics of the eye compared to primary gaze, however these studies have not investigated changes in ocular optics in downward gaze. A range of biomechanical changes may occur when we adopt a downward gaze that could result in changes of ocular aberrations.…”
Section: Introductionmentioning
confidence: 99%
“…Error bars are often large within refractive groups [14,15], and it remains unclear how much of this variability can be attributed to interindividual variability and how much to "noise" of the measurement technique. Turning the eye does not seem to induce significant differences in peripheral refraction and aberrations [16,17]. Nevertheless, the extensive measuring procedure makes it difficult to exclude effects of accommodation when the eye is not cyclopleged.…”
Section: Introductionmentioning
confidence: 98%